The Experience of Disclosure and Concealment of One’s Mental Disorder - Gaižiūtė, Indrė; Kaluževičiūtė-Moreton, Greta; Klimaitė, Vaiva (Psichologija, 2023)
Although disclosure of one’s experience of mental disorders is an important factor in the recovery process, this topic is not well understood or studied in scientific research. This study seeks to describe and analyse the experience of disclosing and concealing information about mental disorders. The participants were 5 men and 5 women (age 24–53) experiencing a form of mental disorder and receiving treatment for at least one year. Data was collected through semi–structured interviews and analysed using thematic analysis. The results showed that the decision to disclose information about one’s mental disorder is motivated by the desire to make oneself feel better, the need to justify oneself, and as a way to educate others. In contrast, concealment is used as a way to avoid stigmatising reactions and inflicting discomfort in other people. Our study results reflect a tendency among the participants to be selective about the information disclosed as well as the people it is disclosed to; however, the latter aspects of disclosure are open to change throughout time. Finally, participants in the study reported the positive value of both disclosing and concealing information about their mental disorder. The results of this study contribute to a better understanding of disclosure and concealment of one’s mental disorder and may be useful for those who interact with or provide support to people with mental disorders.